7y-6-2y+2=0

Simple and best practice solution for 7y-6-2y+2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y-6-2y+2=0 equation:


Simplifying
7y + -6 + -2y + 2 = 0

Reorder the terms:
-6 + 2 + 7y + -2y = 0

Combine like terms: -6 + 2 = -4
-4 + 7y + -2y = 0

Combine like terms: 7y + -2y = 5y
-4 + 5y = 0

Solving
-4 + 5y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 5y = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 5y = 0 + 4
5y = 0 + 4

Combine like terms: 0 + 4 = 4
5y = 4

Divide each side by '5'.
y = 0.8

Simplifying
y = 0.8

See similar equations:

| 2x+4(x+16)=130 | | 8m^2-11m+3=-5 | | 2r^2+3r-2+5r^2+8= | | (3x+9)(4x+7)= | | h(t)=-16t^2+60t+4 | | 2q+4-7+8q-q= | | 2x^2+11=-13 | | -2(v+3)+v=-30 | | -5p+32=12 | | 4g=692 | | 10t-12t=8 | | 3.5d+9.75=1+5.25d | | -2t+5=-7 | | a+34=57 | | -1(6x-2)=5(x+1) | | 4(10x+3)=-68 | | 3(c+7)-c= | | 4+8=-3 | | 6-x-x=17 | | 4a-3=9+a | | -19.4-15d+22d=44 | | cos(5x)+cos(5y)=0 | | 3(x-3)=2(6+x)1/2 | | y=x(2)-2x+3 | | 2k-10-7=8 | | 5(-2x-4)=97+3(4x+5) | | logx+log(4x-3)=1 | | 13=x^2-14x | | 32w-8w+21=69 | | 9y-15=-3(y+7) | | 22590-x=17500 | | 46t-9t+7t-40t+12=96 |

Equations solver categories